UJI COBA FILTER KERAMIK DENGAN CAMPURAN SEKAM, BEKATUL, SERBUK GERGAJI dan KOLOID PERAK DALAM PENGOLHAN AIR - Slamet Hariyadi; Margono .; Didik Sugeng Purwanto (GEMA LINGKUNGAN KESEHATAN, 2013)
Many people commonly are using surface water as the main source for clean and drinking water.Ironically, the quality of surface water decreases from time to time due to domestic and industrialpollution. Earthen pots with colloidal silver applied on their surface created simple coated filters where thesilver coating serves as a disinfectant that render the product water ready for consumption.This is a descriptive pre-experimental research, using one group pretest-posttest design, that isto evaluate water treatment to produce water ready for consumption by analyzing the water quality,before and after treatment with the unit, especially with regard to physical and microbioloqical parametersaccording to PERMENKES/N0.492/ MENKES/PER/IV/2010re: drinking water quality requirements.Measurements indicated that pottery filter with a mixture of clay-bran 40% is fastest flowfiltration flow filtration, which meant 5 liters of filtrate out in 21 minutes. Meanwhile a mixture clay-wood20% with an average flow of (Q) 0.254 It / jm was slowest.However clay-rice bran mixture 20% was themost is stable. Result of microbiological examination on pond water (raw condition) indicated a Coli MPNIndex of 2400, and E Coli index of 1600. After filtration with six pots coated with colloidal silversignificant reduction ini microbiological parameter was observed, indicated by MPN. Coliand E Coli indicesof O. Initial (physical) condition of the pond water have indicated no odour, no colour, no taste, and theturbidity level was 11.78 NTU, TDS level was 142mg/L, temperature was 27°C and pH 5.5. After passingthrough six filter pots coated with silver colloids, physicsl parameter i.e. TDS and turbidity decreased, andpH was normal.With respect to Permenkes No. 416/1990 and Permenkes No. 492/2010 on requirements forpotable water and drinking water respectively, suggestion for follow up research on filter pots coated withcolloidal silver pertaining to the chemistry parameters.Keywords: clay pot tilters, colloidal sitver. Coliform, TDS, turbidity, pH, cotor; temperature,odour and taste.